The effects of text structure on students’ use of comprehension strategies and cognitive outcomes during science text processing - Hunsu, Nathaniel J.; Adesope, Olusola; McCrudden, Matthew T. (Frontiers in Education, 2023)
This study investigated the effect of refutation text structure on reading processes and learning. Undergraduate biology students (n = 116) who had high or moderate misconceptions were randomly assigned to read either a non-refutation text, a simple refutation text, or an elaborated refutation text that addressed commonly held misconceptions about genetic biology. Participants’ were prompted to think-aloud and type their thoughts as they read the text. Typed verbal responses were coded for the use of paraphrasing, bridging inferences, and elaborations. The results showed that the simple and elaborated refutation texts promoted the use of bridging inferences, and the elaborated refutation text promoted the use of elaborations compared to the non-refutation text. Neither text type nor misconception status had a significant effect on post-learning outcomes. These results suggest that refutations with illustrative examples can increase the use of cognitive processes that support comprehension.